If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2v + -1 = 1 Reorder the terms: -1 + 2v = 1 Solving -1 + 2v = 1 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2v = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 2v = 1 + 1 2v = 1 + 1 Combine like terms: 1 + 1 = 2 2v = 2 Divide each side by '2'. v = 1 Simplifying v = 1
| -1-2x(1-7)=8 | | -36.8+9.2x= | | 18x+40(x-3)=468 | | 3x(x+10)=99 | | 9=n/13 | | (4x-11)-(-16x-17)= | | 4x^2+25y^2-100y=0 | | 3*(-1)+2*2-3x=-2 | | 3(t-4)=-2(t-3)+14 | | (X-4)(x+12)= | | 2x-21=x+4 | | x^2+17=19 | | 40x-18(x-3)=468 | | y+6.2=9.1 | | 63=c-21+2c | | 3/6=/8 | | 16+x=42 | | 3.29-0.223= | | 4t^2-20t-60=0 | | 2sin(30+x)=3cosx | | 2+p=2 | | 5n-6=7 | | ln(x)+ln(1.1675x)=5.28 | | 5x-6=93-6x | | 5t+4=11 | | -14=x/2 | | (3x-9)(2x-2)= | | 4.500+60v=50(100+v) | | 4(13-y)+2y=36 | | -42+14x=4y | | 3y+2x-7+12-6x+4y=56-45x+2y | | (c+2)=5(c+1)-7 |